The Effect Of Perceived Supceptibility (Intention) On Voluntary Counselling And Testing Of HIV Among Homosexsual : Meta Analisis - Yuli Astuti; Wiwik Intan Palina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
HIV-AIDS is a include transmission transfusion infection, and one of part health problem in society. The incidence of HIV-AIDS increase every year. Based on study literature homosexual is a high risk group factor. One of the government progams to reduce incidence HIV-AIDS is to carry out VCT. Behaviour is influence by many factors, one of them is perceived supceptibility (intention) on TPB. Intention in the use of VCT services was defined as the desire or inclination of someone to use or not to use VCT services. This research to determine estimated effect on VCT behavior among homosexsual by meta-analysis. Meta-analisis was carried out by searching for articles and database from Google Scholar, PubMed, Springer Link, dan Research Gate. The key word used are “Theory Planed Behavior” OR “TPB” OR “Intention” AND “VCT HIV” OR “HIV counselling” AND “Homoseksual” OR “Gay” OR “MSM”. The inclusion criteria in this study were full text articles from 2011-2020,with cross sectional study design. Analysis articles using RevMan 5.3. The total number of articles analyzed was 4. The result of meta-analysis showed that intention had no effect on increasing the implementation of VCT in among homosexsual (aOR= 0.95: 95% CI= 0.62-1.46; p= 0.83) and I2 94%. Intention had no effect to VCT implementation among homosexsual, behaviors to doing VCT are more likely to be controlled  by  habits than  by intentions. Hopefully the next research will be more research for other TPB construct.